2013
DOI: 10.1007/s00296-013-2889-7
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, disease activity, permanent damage and dsDNA autoantibody production in patients with systemic lupus erythematosus

Abstract: The aim was to study the association of smoking with the activity and severity of systemic lupus erythematosus (SLE) and the production of antibodies to dsDNA. The study included 223 SLE patients attending the outpatient clinics at Helsinki University Central Hospital. The history of smoking was obtained by personal interview, and clinical data related to SLE by interview, clinical examination and chart review. The activity of SLE was assessed by the Systemic Lupus Erythematosus Disease Activity Index (SLEDAI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 13 publications
2
23
1
1
Order By: Relevance
“…We have demonstrated lower humoral immune activation in current and past smokers across multiple antibodies. This has been shown previously in periodontal disease, systemic lupus erythematosus, healthy subjects, and in a cohort of 113 Crohn's disease patients using only a single antibody (ASCA) . That past smokers cluster with current smokers in the presence and magnitude of these antibodies suggests that immune down‐regulation may not resolve on cessation of smoking; this remains to be tested with stricter smoking criteria.…”
Section: Discussionsupporting
confidence: 71%
“…We have demonstrated lower humoral immune activation in current and past smokers across multiple antibodies. This has been shown previously in periodontal disease, systemic lupus erythematosus, healthy subjects, and in a cohort of 113 Crohn's disease patients using only a single antibody (ASCA) . That past smokers cluster with current smokers in the presence and magnitude of these antibodies suggests that immune down‐regulation may not resolve on cessation of smoking; this remains to be tested with stricter smoking criteria.…”
Section: Discussionsupporting
confidence: 71%
“…More recently, Gustafsson et al found an association between smoking and an SDI score of >1 (data related to SDI scores of >0 were not available) in a study of the development of pathogenic antiphospholipid antibodies in current and former smokers, but secondhand smokers were not included in the analyses. The study by Ekblom‐Kullberg et al also did not include secondhand smokers and did not assign patients to an “ever” status (current, former, or secondhand smoker) versus a “never” status as the present study does. Further, they found no significant differences in SDI score between current or former smokers versus never smokers.…”
Section: Discussionmentioning
confidence: 87%
“…To emphasize the need for more data regarding the cumulative chronic effects of smoking in SLE, we performed a small systematic review. We found more than 222,000 papers about smoking, but only 6 were directly related to smoking exposure and chronic damage among SLE patients (25)(26)(27)(28)(29)(30). Apart from studies that we may have missed in our short systematic review, it seems that the medical literature does not include much on this subject.…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, further studies with individual monitors capable of measuring exposures in real time should be conducted. Second, individual data on potential confounders, such as body surface area, age, exposure to sunlight, and exposure to cigarette smoke were not available, although the effect of smoking on SLE disease activity has been debated (21,22). Additionally, the possibility of casual results cannot be completely excluded.…”
Section: Discussionmentioning
confidence: 99%